Confidentiality and Integrity of Sensing Data Transmission in IoT Application - Hamad Khalaf, Rafide; Hashim Mohammed, Ahmed (International Journal of Engineering and Technology, 2018)
In the last few years the Internet of Things (IoT) has been developing new ways expected to connect billions of devices in different application of life. The increased numbers of connected devices arÐµ ÐµssÐµntially smallÐµr in sizÐµ and low powÐµrÐµd may be led to generate big data and face the security of data that transmitted. This paper proposed two types of security service for an IoT smart home application, the first security service is confidently which achieved by encrypting all data that sensor send to IoT server using AES-GCM or RSA-OAEP encryption algorithm moreover second security service is integrity all data that sensor send to IoT server which achieved using SHA3-512 encryption algorithm. In order to validate the security of sensor data results, we first had to implement the smart home application which consists of raspberry pi 3 and four sensors, the evaluation result shown a shorter average time 3ms when using AES-GCM algorithm whereas the RSA-OAEP algorithm had taken about 9ms, furthermore the integrity service had taken about 25% of encryption time.Â Â